THE OPTIMIZATION OF STAINLESS STEEL 304 AND 316 WELDED JOINTS ON CORROSION RATE BY THE TAGUCHI METHOD - Wijaya, Muhammad Agus; Arifin, Amir; Gunawan, Gunawan (Asosiasi Peneliti Sriwijaya, 2025)
The Water Treatment Plant (WTP) is a water purification system designed to meet the water demands for power generation and operational requirements in the petrochemical industry. The current pipeline network in the Demin Plant unit employs carbon materials with rubber cladding, which presents drawbacks, such as extended recovery times during system failures. To address the issue, the research explored welding SS 304 and SS 316 materials as an alternative to the existing carbon pipes with rubber cladding. The study utilized the Taguchi experimental design method, employing an orthogonal array (L9) table to optimize quality improvement while minimizing costs. The experiment included 9 test specimens with three repetitions, examining four welding parameters, each with three levels. Variance (ANOVA) was analyzed using the Minitab software and manual calculations in Microsoft Excel. The results indicated that the factors influencing the corrosion rate of the specimens include the welding method, electrode type, welding speed, and welding current. ANOVA results showed that the welding method (F-value = 5.9176) and welding current (F-value = 8.3492) significantly affected the corrosion rate, whereas the electrode type (F-value = -3.5949) and welding speed (F-value = -2.8321) did not. A confirmation experiment yielded an optimal corrosion rate of 3.0231 mm/y, lower than experiment number 7.